Ahead of the class: Modules - Starlink Project; Dallas County Community College District ([Dallas, Tx.] : Starlink, 2012)
Module 1: Motivating your students (14:06) -- Module 2: Active classroom strategies (22:55) -- Module 3: Promoting your students's critical thinking skills (23:45) -- Module 4: Assessment (19:23).
Recorded on Sept. 24, 2012.
DVD.
Closed-captioned.
Keywords: Education; Teaching; Learning